TRINITY EMERGENT-ECCLESIOLOGY : SEBUAH TAWARAN EKLESIOLOGI KONTEKSTUAL ERA PASCAPANDEMI COVID-19 - Sherly Masnidar (Sekolah Tinggi Teologi Arastamar Bengkulu, 2023)
The church's identity, before, during, and after the COVID-19 pandemic, is no longer the same. During the COVID-19 era, when the church fully embraced its digital form, many ecclesiology formulations optimistically placed the church's future in the non-institutional digital church. In reality, in the current post-COVID-19 era, the church is returning to its pre-pandemic form, that is, as an institutional church. Based on this phenomenon, this article aims to offer a contextual post-Covid-19 ecclesiology study. To achieve this goal, this article will critique the writings of Selome Kuponu and Adekunle Tayo, which discuss post-Covid-19 practical ecclesiology based on the theological construction of an open church through a study of the Trinitarian-Perichoresis relationship. The outcome of this article is to propose an open ecclesiology based on networked relationships as a proposal for a transformative contextual ecclesiology in the post-pandemic COVID-19 church. Specifically, networked relationships mean that the church sustains its fellowship both through in-person meetings (analogue) and digital meetings (digital). This article is written based on a qualitative descriptive research methodology that elucidates the essential aspects that need to be developed in our church life in the current post-Covid-19 era through a literature data analysis method.